Why Spiritual Leadership is Such an Important Component of the Company: Scoping Overview - Tri Sinarti; Sopiah (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2023)
Spiritual leadership in an organization is a topic that is receiving increasing attention. Spiritual leadership proliferated and gained popularity in the 1990s. Several authors have emphasized the importance of spiritual leadership. This article examines empirical studies highlighting the importance of spiritual leadership from the perspective of companies and their employees. This study uses the scoping review method of data obtained from manuscripts published between 2009 and 2022, found 24 publications. This review summarises 14 years of spiritual leadership research while also considering the context, nature, and contemporary spiritual leadership literature. This study tries to collect data that shows the significant influence of spiritual leadership on groups and their constituents. The research results show that spiritual leadership generally has a beneficial and sizeable impact on the organisation's and its members' growth. This study highlights the critical role of spiritual leadership in organizations, including the organization and its constituents.